Family caregivers’ experience of caring for patients undergoing hemodialysis: A qualitative study at Muhimbili National Hospital in Dar es Salaam, Tanzania - Ally Halfan Magenge; Menti Lastone Ndile; Francis Furia (PLoS ONE, 2025)
Background The number of patients with chronic kidney disease requiring hemodialysis services is growing in Tanzania. Considering patients undergoing hemodialysis are outpatients, family caregivers fill the gap of caring and support during the lifelong treatment process. Limited information exists especially in the context of Tanzania regarding the challenges the family caregivers encounter during their involvement in the caring process. This study aimed to explore family caregivers’ experience of caring for patients undergoing hemodialysis at Muhimbili National Hospital, Dar es Salaam, Tanzania. Methods A qualitative study employing phenomenological design was conducted. Fourteen family caregivers of patients receiving hemodialysis services at Muhimbili National Hospital were purposively selected. Semi-structured in-depth interviews were used for data collection. Interviews were audio-recorded and transcribed verbatim. Data were analyzed following Braun and Clarke’s six phases of thematic analysis. Results The study uncovered four key themes from fourteen interviews. The themes were: 1) Family caregivers and providers’ interaction, focusing on interpersonal and professional relationships 2) The status of dialysis treatment, describing access and availability of resources for the provision of hemodialysis services 3) Impact of long-term care, touching issues of emotional, physical and social-economic impact to family members and 4) Coping with caring, describing internal and external mechanisms family members use to adjust to demanding situation of caring their loved ones. Conclusion Caring for patients receiving hemodialysis treatment burdens family caregivers, impacting their livelihood and resources. Healthcare providers need to build a close working relationship with family caregivers to understand their challenges and needs and help build their coping capacities. Additionally, dialysis service coverage issues such as affordability, accessibility, and availability need to be addressed to reduce the caring burden on family caregivers.